Analisis perbandingan kefahaman konsep taubat dalam kalangan masyarakat Melayu Muslim dan Melayu Protestan di daerah Temburong, Negara Brunei Darussalam / Sri Rahayu Dollah - Sri Rahayu , Dollah (2017)
This study focuses on two groups of the Malay communities from different religious background. In the context of Brunei Darussalam (BD), the notion of Malay is defined differently compared to the definition of Malay from the Malay Archipelago perspective. The Constitution of Brunei Darussalam 1959 conceptualize the word Malay as a origin people of Brunei regardless of their religions and ethnics. This include Muslims as majority and non-Muslims such as Christian Protestan, Catholics, Buddhists and Pagan. From a religiosity perspective, Malay Muslims and Malay Protestants share some similarities particularly in practicing the concept of repentance as an alternative solution in resolving the issues related to soul, social and global. Therefore, this study aims to investigate the concept of repentance, its practices and understanding from Muslims and Christian Protestants point of views. This include analyzing their perceptions, implementations and comparative analysis from both targeted groups. Mixed method approach, combining quantitative and qualitative analysis are employed for data collection in both field work and library research. Qualitative approach in this study employ observations, interviews and open ended questions. Whereas, quantitative approach utilize questionnaire which are distributed among Malay Muslims and Malay Protestants in the district of Temburong, Brunei. Conceptually, the concept of repentance, its definition, religious rulings and the purpose of repentance have some similarities between Islam and Christian Protestan perspectives. However, the perspective of repentance differs between Islam and Christian Protestan in their characteristics, purposes, authority of granting forgiveness and the implementation. Findings of qualitative data show that both Malay Muslims and Christians have some similarities in their perception of repentance and their understanding in seeking forgiveness, however, both groups are differs in their way of practicing repentance in the society. Findings of the quantitative data reveal different levels of understanding the concept of repentance. In addition, it is found that the knowledge of repentance is relatively high in both groups of Muslims and Christians. However, the mean score of repentance implementation among Malay Muslims are higher compared to Malay Protestants. Furthermore, the practice of repentance is more appealing among Malay Muslims group even though there are few basic points that require more attention among them. In comparison, Malay Protestan understand less about the concept of repentance due to a flexibility concept of repentance implementation in Christianity and it is free from religious ruling which impacted their way of life.